Analysis of the Influence of Strategies to Increase Human Resources Motivation in Education of Global Competitivenessa - Bambang Ismaya, Abduloh , Rachmat Ramdani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Motivation, Influence Analysis, and Implementation of Strategies for Increasing Global Competitiveness of Human Resources in Kab. Karawang. Aims to identify and obtain empirical evidence about the influence of motivation and the implementation of strategies to increase Human Resources global competitiveness Kab. Karawang. Theoretically, the motivation for the implementation of the human resource strategy implemented in Karawang establishes policies to achieve institutional goals in improving the quality of Human Resources in the field of education which has an influence on the quality of people's lives. This study wants to answer whether that also applies to the context in Karawang Regency. This research method is carried out using descriptive and verification methods. The sampling technique used is cluster proportional random sampling, the sample determination uses a formula developed by Isaac and Michael, with a population of 10 classes with a sample size of 30 respondents. The research was conducted in Karawang Regency. The results of the study are based on the t-test results table above, in column t it can be read that the proof of the hypothesis is as follows: The effect of motivation on Human Resources Education is partially 0.476 with a significance of 0.006 which is smaller than 0.05, so H0 is rejected and H1 is accepted. The effect on human resources education is partially 0.336 with a significance of 0.028 which is greater than 0.05. So, H0 is rejected and H1 is accepted. From Table 6 it is known that the regression equation obtained is as follows: Y = 4.604 + 0.476X1 + 0.336X2 + e